THE RELATIONSHIP BETWEEN CONFIDENCE AND WORKING READINESS OF STUDENTS IN THE CITY OF PADANG - Krisnova Nastasia; Misrofingah; Budi Akhmad Tarigan; Hilda Mary; Indriyenni (Enrichment : Journal of Management, 2022)
This study aims to see whether there is a relationship between self-confidence and working readiness in final year students majoring in jinayah and siyasa, sharia faculty, State Islamic Institute (IAIN) Imam Bonjol Padang. The population in this study were final year students who were taking thesis courses totaling 50 people. The sampling technique used in this study is purposive sampling, namely the purpose of the sample is to take the subject not based on strata, random but based on a specific purpose. The measuring instrument used is the self-confidence scale and the work readiness scale. The data analysis method used to test the hypothesis in this study is to use product moment (person) correlation, which shows that there is a significant relationship between self-confidence and working readiness, meaning that the higher the self-confidence, the higher the working readiness of final year students majoring. jinayah and siyasa of IAIN Imam Bonjol Padang. It means that the research hypothesis is accepted.